2013 election to German Bundestag from the viewpoint of direct democracy - Andranik S. Tangian (Hans-Böckler-Stiftung, Wirtschafts- und Sozialwissenschaftliches Institut (WSI), 2013)
The outcomes of the 2013 German Bundestag (federal parliament) are analyzed from the viewpoint of direct democracy. For this purpose, the party positions on 36 topical issues are compared with the results of public opinion polls, and the party and coalition indices of popularity (the average percentage of the population represented) and universality (frequency in representing a majority) are constructed. It is shown that the 2013 election winner, the union of two conservative parties CDU/CSU with their 41.6% of the votes, is the least representative among the four parties eligible for parliament seats (with > 5% of the votes). The most representative among the eligible ones is the left party DIE LINKE that received only 8.6% of the votes. It is concluded that voters are not very consistent with their own political profiles, disregard party manifestos, and are likely driven by political traditions, even if outdated, or by personal images of politicians. Moreover, the actual practice of coalition formation further aggravates the low representativeness of the parliament. Thereby it is shown that representative democracy, as it is, guarantees no adequate representation of public opinion even in Germany with its multiparty system and strong socialdemocratic traditions. To bridge approaches of representative and direct democracy, an alternative election procedure is proposed. For illustration, it is hypothetically applied to redistribute the Bundestag seats with a considerable gain in its representativeness.
Keywords: D71; 330; representative democracy; direct democracy; elections; coalitions; theory of voting; mathematical theory of democracy; indices of popularity and universality